Methanol-based acetoin production by genetically engineered Bacillus methanolicus. Issue 3 (8th January 2020) - Drejer, Eivind B.; Chan, Dennis Tin Chat; Haupka, Carsten; Wendisch, Volker F.; Brautaset, Trygve; Irla, Marta
Abstract : Establishment of sustainable technology for methanol-based production of acetoin by metabolically engineered Bacillus methanolicus . Abstract : Methanol is an attractive alternative non-food feedstock for industrial fermentations that can be used instead of sugar-based raw materials. Here, the thermophilic and methylotrophic bacterium Bacillus methanolicus MGA3 was metabolically engineered to produce the platform chemical ( R )-acetoin from methanol at 50 °C. Three different heterologous alsSD / budAB operons, each encoding acetolactate synthase and acetolactate decarboxylase, were functionally expressed under control of an inducible promoter in B. methanolicus MGA3, resulting in up to 0.26 ± 0.04 g L −1 of ( R )-acetoin titer in shake flask cultivations. To further improve acetoin production, a total of six different genes or operons were expressed in the acetoin producing strains to increase supply of the acetoin precursor pyruvate. In particular, expression of a gene coding for malic enzyme from Geobacillus stearothermophilus in combination with the isocitrate lyase gene from B. methanolicus MGA3 increased acetoin titers 1.6-fold up to 0.42 ± 0.01 g L −1 which corresponds to 0.07 g g −1 methanol. This resulted in an MGA3 strain overproducing 4 recombinant enzymes in total from two different plasmids with two distinct antibiotics resistance markers, demonstrating the increased complexity of metabolic engineering allowed by newly developed genetic tools for this organism. To our knowledge, this is the first demonstration of microbial production of acetoin from methanol.